Pemanfaatan Smart PTSL Sebagai Instrumen Pengumpul, Pengolah dan Pengintegrasi Data Fisik dan Data Yuridis Pendaftaran Tanah Sistematis Lengkap - Hasrul Ahmad; Mr Sutaryono; Nuraini Aisiyah (Sekolah Tinggi Pertanahan Nasional, 2020)
One of the obstacles in achieving the target of PTSL is the difficulty in integrating physical and juridical data, as effect of inefficiency of data collection. This research aims to explain the benefit of using SMART PTSL as an instrument to collect, process and integrate physical and juridical data and to test relative accuracy of area, shape and position of land parcels mapped using SMART PTSL, compared to land parcels download from Geo-KKP. Mixed method by combining quantitative and qualitative methods was implemented. The sample was determined using purposive sampling method. The results show that SMART PTSL give benefit in (a) simplify the process of physical and juridical data integration; (b) shorten the process of physical and juridical data verification; (c) simplify data entry to KKP PTSL. The result of relative accuracy comparison of area, shape and location show that from 34 land parcels, 11 parcels were meet the tolerance, while 23 parcels were not. The tolerance was calculated using equation 0,5 ?L. Moreover, the result of tolerance calculation was affected by measurement method.